Serenata a treasury of Kapampangan songs : traditional songs contributed by the common folk of the Kapampangan Region - Lumanug, Edwin (Angeles City Holy Angel University, Juan D. Nepomuceno Center for Kapampangan Studies, 2009)
"Compilation of lyrics and music notations of over 100 traditional Kapampangan songs collected from all over Pampanga."
Keywords: Vocal music -- Philippines -- Pampanga -- History and criticism; Folksongs -- Philippines -- Pampanga -- History and criticism; Pampangos (Philippine people) -- Music